AGROFORESTRI UNTUK PENGEMBANGAN FOOD ESTATE : Perspektif Lingkungan - Budiman Achmad; Dian Diniyati (Jurnal Agroforestri Indonesia, 2021)
The high population growth of 3.26 million people per year and the shrinking land for agriculture have caused sufficient food supply to become a problem. As a tropical country, all regions of Indonesia have the potential to develop various types of plants, including carbohydrate-producing crops to ensure national food security. Food crop development programs by the government through food estate projects need to consider various factors so that the goal of achieving food security can be successful. Considering that this project is very strategic and the target that is cold to achieve is very large with a limited time, the easiest way to develop it may be using a monoculture pattern. This pattern is considered very vulnerable to pest and disease attacks, with a very large risk. This paper reviews environmental factors related to the development of carbohydrate-producing plants so that the expected economic function can be achieved. There are three interrelated pillars in the sustainable development goals (SDGs), namely the social,  economic, and environmental pillars. The method used is to review the literature on food crop development using agroforestry models from various sources, domestic and foreign. The results of the study strengthen the evidence that the agroforestry pattern can provide environmental pillars that become an enabling factor for the achievement of economic goals, namely the achievement of the development of carbohydrate-producing plants through food estate projects. The results of the study also concluded that the agroforestry pattern brings at least six advantages, namely increasing land productivity, suppressing the development of plant pests and diseases, contributing to climate change mitigation, increasing soil fertility, improving soil and water conservation functions, and being a therapeutic medium (forest healing). Based on these results, it is highly recommended to apply the agroforestry model to food estate development projects